Researching at the community-university borderlands: Using public science to study policing in the South Bronx - Brett G. Stoudt; María Elena Torre; Paul Bartley; Evan Bissell; Fawn Bracy; Hillary Caldwell; Lauren Dewey; Anthony Downs; Cory Greene; Jan Haldipur; Scott Lizama; Prakriti Hassan; et al. (Arizona State University, 2019)
This article is a case study of the Morris Justice Project (MJP), a participatory action research (PAR) study in a South Bronx neighborhood of New York City (NYC) designed to understand residents' experiences with and attitudes towards the New York Police Department (NYPD). An illustration of public science, the research was conducted in solidarity with an emerging police reform movement and in response to an ongoing and particularly aggressive set of policing policies that most heavily impacts poor communities and communities of color.  The case study describes a set of ongoing participatory, research-action, "sidewalk science" strategies, developed in 42 square blocks of the South Bronx, designed to better understand and challenge the ongoing structural violence of the carceral state. Collaboratively written with members of the Morris Justice collective, we tell our story across three sections that outline the genesis of the project, describe our major commitments, and offers PAR and public science as a possible "intervention" in traditional university practice.